2017
DOI: 10.1530/rep-17-0016
|View full text |Cite
|
Sign up to set email alerts
|

DHEA protects mitochondria against dual modes of apoptosis and necroptosis in human granulosa HO23 cells

Abstract: Because ovarian granulosa cells are essential for oocyte maturation and development, we validated human granulosa HO23 cells to evaluate the ability of the DHEA to prevent cell death after starvation. The present study was aimed to investigate whether DHEA could protect against starvation-induced apoptosis and necroptosis in human oocyte granulosa HO23 cells. The starvation was induced by treatment of serum-free (SF) medium for 4 h Starvation-induced mitochondrial depolarization, cytochrome release and caspase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 43 publications
1
33
0
Order By: Relevance
“…The three major forms of estrogens in humans are estradiol, estrone, and estriol, with estradiol being the predominant form [ 31 , 32 , 33 , 34 , 35 ]. The ovary is the main source of estrogen in the premenopausal period, and granulosa cells are the key cells to produce estrogen [ 36 , 37 , 38 , 39 , 40 ]. Estrogen is also synthesized in skin tissue [ 41 ], presenting a concept termed “intracrinology” [ 42 ].…”
Section: Estrogen and Estrogen Signalingmentioning
confidence: 99%
“…The three major forms of estrogens in humans are estradiol, estrone, and estriol, with estradiol being the predominant form [ 31 , 32 , 33 , 34 , 35 ]. The ovary is the main source of estrogen in the premenopausal period, and granulosa cells are the key cells to produce estrogen [ 36 , 37 , 38 , 39 , 40 ]. Estrogen is also synthesized in skin tissue [ 41 ], presenting a concept termed “intracrinology” [ 42 ].…”
Section: Estrogen and Estrogen Signalingmentioning
confidence: 99%
“…However, direct action of DHEA on the target organs has been proposed [ 42 , 43 ] but is still inconclusive. Regarding the molecular mechanism, our previous studies revealed that DHEA supplementation could improve mitochondrial function and reduce apoptosis in the cumulus cells [ 44 ] and human granulosa cell line [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, enhancing mitochondrial biogenesis may result in an improvement of oocyte and embryo quality and, subsequently, better pregnancy outcomes because increased mitochondrial energy production may decrease chromosomal aneuploidies, improve embryo cleavage, and reduce cytoplasmic fragmentation [ 52 ]. Our previous studies showed that DHEA could increase mitochondrial function and activity, and reduce apoptosis and cell necroptosis in CCs and human granulosa cell line [ 3 , 4 , 53 ]. In addition, we found that DHEA might slow the aging of CCs [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies demonstrated that mitochondrial function was significantly impaired in cumulus cells (CCs) from the POR group, and in human granulosa cells in vitro from the serum free group compared with the control group [ 3 , 4 ]. Hence, considering the importance of mitochondrial function in the oocyte, it is not surprising that oocyte quality decreases with increasing mitochondrial dysfunction [ 5 ].…”
Section: Introductionmentioning
confidence: 99%